INKLUSIVITAS MASYARAKAT ISLAM PEGAYAMAN MELALUI SISTEM PENAMAAN DIRI - Budarsa, Gede; Ginting, Jonson Handrian (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
A name is a marker of a person's self in a social system. The Pegayaman Islamic Community is one of the Islamic communities in Bali. This Islamic society has integrated various elements of Balinese Hindu culture, including in its self-naming system. They use the naming patterns of the Balinese Hindu community. This research explores the naming patterns of the Pegayaman Islamic community which originates from the Balinese Hindu tradition. By using qualitative methods such as interviews, observations and literature studies, this research reveals that the naming system of the Pegayaman people uses birth order and gender like the Balinese Hindus. Typical Balinese names include Wayan for the first child, Nengah for the second child, Nyoman for the third child and Ketut for the fourth child. This name was then combined with an Islamic name. The naming pattern according to birth order resulted in the names Wayan Hasyim, Nengah Zakaria, Nyoman Imamulhayi and Ketut Muhammad. Names according to gender use the name Siti for women and Muhammad for men. This integration of Balinese culture reflects the inclusive attitude of the Pegayaman Islamic community in responding to conditions in Bali, fostering an attitude of tolerance and mitigating tendencies towards religious fundamentalism and radicalism.